Miskonsepsi Materi Bangun Ruang di PGMI 3 UIN Sumatera Utara - Novia Rahmadani Harahap; Rora Rizki Wandini (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This research aims to analyze misconceptions about spatial construction materials at PGMI 3 UIN Sumatra Utara, with a focus on problems that arise in spatial construction materials. The method used in this research was interviews given to 20 students of PGMI 3 UIN North Sumatra. The research results revealed that the majority of respondents had misconceptions regarding understanding spatial building material. In order to overcome this misconception, it is necessary to take a more in-depth learning approach to improve students’ understanding of spatial construction material. Appropriate teaching steps and more intensive practice. This research provides important insights for the development of more effective teaching methods in overcoming misconceptions in spatial material.